Low-dose azathioprine and allopurinol versus azathioprine monotherapy in patients with ulcerative colitis (AAUC): An investigator-initiated, open, multicenter, parallel-arm, randomised controlled trial. (March 2022) - Kiszka-Kanowitz, Marianne; Theede, Klaus; Thomsen, Sandra Bohn; Bjerrum, Jacob Tveiten; Brynskov, Jørn; Gottschalck, Ida Benedikte; Akimenko, Elena; Hilsted, Karen Lisa; Neumann, Anders; Wildt, Signe; Larsen, Lone; Munk, Jens Kristian; et al.
Summary: Background: Retrospective studies suggest that for patients with ulcerative colitis (UC) combination therapy with low-dose azathioprine and allopurinol (L-AZA/ALLO) may result in higher remission rates than monotherapy with azathioprine (AZA). We prospectively investigated the effects of these drugs for remission in patients with moderate-to-severe UC. Methods: Open-label, unblinded, randomised, controlled, investigator-initiated, multicentre study conducted at eight hospital sites in Denmark. Adult patients with established UC, who were steroid dependent/refractory, thiopurine naïve, had a normal thiopurine methyltransferase, and achieved remission with steroids or infliximab were eligible for inclusion. Patients were randomly assigned by the investigators (1:1) to 52 weeks of treatment with once daily oral AZA (median dose 50 mg) combined with ALLO 100 mg versus AZA monotherapy (median dose 200 mg), using a computer-generated randomisation list with blocks of six. The trial was open without masking. All randomised patients who received at least one dose of study drug were included in primary and safety analyses (intention to treat population). The primary outcome was steroid and infliximab free remission after 52 weeks, defined as a Mayo Score of ≤1 and no rectal bleeding. The trial is completed and is registered in ClinicalTrials.gov (ClinicalTrials.gov NCT03101800). Findings: Between January 9, 2017 and February 10, 2021, 47 patients were randomised to l -AZA/ALLO and 42 to AZA and received at least one dose of the study drug. After 52 weeks, 20 of 47 (43%) patients in the l -AZA/ALLO group and nine of 42 (21%) patients in the AZA group achieved remission (odds ratio 2·54 [95% CI 1·00 to 6.78, p  < 0·048]). Fourteen patients (30%) in the l -AZA/ALLO group and 16 (38%) in the AZA group were withdrawn from the study due to adverse events. Interpretation: This study suggests that after one year l -AZA/ALLO therapy may be associated with a beneficial effect on steroid- and infliximab-free clinical remission in patients with moderate-to-severe UC and should be considered as first line therapy. Funding: Funding for AAUC was provided by The Capital Region of Denmark ( Regionernes Medicinpulje (6062/16)).